Self-Threat and Product Failure: How Internal Attributions of Blame Affect Consumer Complaining Behavior - Dunn, Lea; Dahl, Darren W. (Journal of Marketing Research, 2012)
Previous research in complaining behavior has focused on product or service failures in which the organization is responsible for the failure. In these cases, researchers have found that consumers feel better about the product failure after complaining about it. In contrast, the authors show that when consumers are to blame for product failure, complaining has a detrimental effect on consumer reactions to the product. In this context, self-threat from the product failure is shown to motivate defensive processing in both the content of complaints and the subsequent downstream product evaluations. The authors establish the role of self-threat in product failure in two ways: (1) by varying the intensity of the threat from product failure and (2) through mitigating negative outcomes through self-affirmation. The article concludes with discussion on how these findings can benefit companies and where this research could seed opportunities for subsequent investigation.